2002
DOI: 10.1046/j.1354-1013.2002.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of climate change on selected agricultural crops in north‐eastern Austria

Abstract: The vulnerability and adaptation of major agricultural crops to various soils in north‐eastern Austria under a changing climate were investigated. The CERES crop model for winter wheat and the CROPGRO model for soybean were validated for the agrometeorological conditions in the selected region. The simulated winter wheat and soybean yields in most cases agreed with the measured data. Several incremental and transient global circulation model (GCM) climate change scenarios were created and used in the study. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(72 citation statements)
references
References 24 publications
5
62
0
5
Order By: Relevance
“…Challinor and Wheeler [28] showed that average and high temperatures during the growing season were not the main determinants of soybean seed yield, but extreme temperatures had a negative effect on yield. A similar approach to climate change and soybean yield has been presented by Vasselin et al [29], indicating the effectiveness of soybean adaptation in western parts of Europe. Using the CROPGRO model, these authors showed that incremental warming, in combination with an increase in precipitation, leads to higher soybean yield.…”
Section: Impact Of Weather On Total Dry Matter and Seed Yieldmentioning
confidence: 97%
“…Challinor and Wheeler [28] showed that average and high temperatures during the growing season were not the main determinants of soybean seed yield, but extreme temperatures had a negative effect on yield. A similar approach to climate change and soybean yield has been presented by Vasselin et al [29], indicating the effectiveness of soybean adaptation in western parts of Europe. Using the CROPGRO model, these authors showed that incremental warming, in combination with an increase in precipitation, leads to higher soybean yield.…”
Section: Impact Of Weather On Total Dry Matter and Seed Yieldmentioning
confidence: 97%
“…As arthropods can have a strong influence on nutrient cycling processes (Seastedt and Crossley, 1984), they are also very important for ecosystem net primary production (Abbas and Parwez, 2012). Predicted longer drought intervals between rainfall events will increase drought stress for crops while changes in the amount and timing of rainfall will affect yields and the biomass production of crops (Eitzinger et al, 2001;Alexandrov et al, 2002;Thaler et al, 2008). These changes in vegetation structure and quality will also affect associated arthropods (Andow, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are many potential ways to introduce management-level adaptation options for cropping systems, thus dealing with projected climate changes [3][4][5]. These adaptations include strategies such as altering varieties/species to those with more appropriate vernalization requirements and/or with resistance to heat shock and drought.…”
Section: Introductionmentioning
confidence: 99%